Coral skeletal luminescence records changes in terrestrial chromophoric dissolved organic matter in tropical coastal waters - Kaushal, Nikita (2021)
Terrigenous dissolved organic matter (tDOM) carried by rivers represents an important carbon flux to the coastal ocean, which is thought to be increasing globally. Because tDOM is rich in light‐absorbent chromophoric dissolved organic matter (CDOM), it may also reduce the amount of sunlight available in coastal ecosystems. Despite its biogeochemical and ecological significance, there are few long‐term records of tDOM, hindering our understanding of its drivers and dynamics. Corals incorporate terrestrial humic acids, an important constituent of CDOM, resulting in luminescent bands that have been previously linked to rainfall and run‐off. We show that luminescence green‐to‐blue (G/B) ratios in a coral core growing in waters affected by peatland run‐off correlate strongly with remote sensing‐derived CDOM absorption. The 24‐year monthly‐resolution reconstructed record shows that rainfall controls land‐to‐ocean tDOM flux from this protected peatland catchment, and suggests an additional impact by solar radiation, which degrades tDOM at sea.